The Influence of Using Instagram Social Media on the Morals and Achievement of Students at SMP Negeri 1 Bandar Lampung - Tina Fitriani; Imam Syafe’I; Nanang Supriadi (CV. Creative Tugu Pena, 2024)
This research reveals the impact of using Instagram social media on the morals and achievement of students at SMP Negeri 1 Bandar Lampung. A quantitative survey method was used with a population of 1012 students, and a sample of 91 respondents was selected using proportionate stratified random sampling technique. The results of data analysis using SPSS 16.0 show that the use of Instagram has a significant negative influence on student morals by 12%, which is influenced by the potential for cyberbullying and content that does not comply with ethical values. The use of Instagram also has a negative impact on student learning achievement by 5.5%, caused by impaired concentration and negative social-emotional influences. However, good morals make a positive contribution of 12.3% to student learning achievement, indicating that high discipline and learning motivation can improve academic results. The practical implication is the need for moral education and parental supervision to direct positive social media use for students.